Rounding of irregular polymer particles in a downer reactor - Sachs, Marius; Schmidt, Jochen; Toni, Franziska; Blümel, Christina; Winzer, Bettina; Peukert, Wolfgang; Wirth, Karl-Ernst (Procedia Engineering 102, 2015)
In the past additive manufacturing processes relying on beam-based methods such as selective laser sintering (SLS) of polymers were almost exclusively applied for the generation of prototypes. In recent years, however, these methods are increasingly applied in the serial production of e.g. special parts to be used in the automotive industry. With this increased relevance in industrial applications, the demands on the powder material increased as well [1]. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. In consequence, there is a need for fine powders of different polymers showing good powder flowability and high bulk density. Currently, the commercial availability of polymer powders for SLS is very limited and the production processes are still not reliable enough due to poor powder characteristics. Within this contribution a process for the production of spherical polymer micro particles showing good powder flowability is presented [2]. It has been recently shown [3] for different materials that commercially available polymer granules can be ground down to the micron size range by a wet grinding process. Due to the grinding process the produced micron-sized particles are in a chiseled state, which leads to a bad flowability of the powder material. To overcome this problem the single particles are melted in a heated downer reactor and spherical particles are obtained by using the effect of the surface tension [3]. The rounding of ground PS microparticles was performed in a downer reactor with a length of 1,600 mm and a diameter of 25 mm. The reactor temperature was set 100 °C above the melting temperature of the treated material. The laminar flow regime in the downer reactor allows a well-defined residence time of particles and the surrounding gas [4]. The design of the downer reactor allows transferring the polymer particles in the molten state whilst avoiding contact between the single particles and between molten particles and the reactor wall. The mechanism of the rounding process in dependence of particle size, interfacial tension and melt viscosity will be shown within a sintering model [6]. The influence of residence time and overall solids density in the downer reactor on the particle shape and on the flowability of the bulk material is shown. Estimates from the sintering model allow for a reliable reactor design.<br
Keywords: additive manufacturing; particle rounding; downer reactor; polymers